La Línea Negra como reconocimiento de territorios ancestrales de las comunidades indígenas de la Sierra Nevada de Santa Marta (2020)
Respect for the ancestral territories of the ethnic communities in Colombia has represented a historical point of social friction and constant violence between the different protagonists of violent conflicrt in our country. This text approaches and addresses the normative and jurisprudential plexus related to the protection of the sacred spaces of the Arhuaco, Kogui, Wiwa, and Kankuamo peoples of the Sierra Nevada de Santa Marta, set down or delimited in what these ethnic communities have called the “Black Line” (Séshizha, in the Kagaba language of the Kogui people; Shetana Zhiwa, in the Damana language of the Wiwa people; or Seykutukunumaku, in the Iku language of the Kankuamo people), a spiritual, cultural, and physical concept of the Law of Origin. The recognition by the Colombian State of the indigenous communities of the Sierra Nevada de Santa Marta, and of their sacred and ancestral sites, through various actions of the branches of public power –administrative acts and court decisions– is a great step towards understanding the importance of ethnic minorities, advocating for the respect and conservation of natural resources and the relevance of both their material and spiritual lives. For this reason, it is appropriate to study whether the normative scaffolding is sufficient and adequate for the preservation and maintenance of the sacred sites that comprise the “Black Line”, which is found in the ancestral memory of the spiritual authorities of our “elder brothers”.